IMPLEMENTASI PERAN PEREMPUAN:PERSPEKTIF ISLAM DALAM DUNIA PENDIDIKAN - hasim, sarifa suhra (An - Nisa`, 2010)
abstract: It is generally atmitted that man and woman live mutuallyironically,stome people restrict the role pf women to certain comesticareas. They set them in secondary and marginal position. In realitywomen have a,extensive main roles in this universe. Even, ,some of them arebetter than men in intelligence, coirage.leadership. ,and education.Their roles obviously should be in appropriate boundaries withoutviolating cultural and religious values. With regard to this position, It is undeniable that islam is the main pioneer that women position properly in privileged proportion and at equal level with men,i.e. equals in human dignity. Islam guarantees womenâs rights comperehensively as free and independent individuals in domestic area as well as in public sector.